In vivo targeting of adult neural stem cells in the dentate gyrus by a split-cre approach - Beckervordersandforth, Ruth; Deshpande, Aditi; Schäffner, Iris; Huttner, Hagen; Lepier, Alexandra; Lie, Dieter Chichung; Goetz, Magdalena (Stem Cell Reports, 2014)
We describe the labeling of adult neural stem cells (aNSCs) in the mouse and human dentate gyrus (DG) by the combinatorial expression of glial fibrillary acidic protein (GFAP) and Prominin1, as revealed by immunohistochemistry. Split-Cre-based genetic fate mapping of these double-positive cells in the adult murine DG reveals their NSC identity, as they are self-renewing and contribute to neurogenesis over several months. Their progeny reacts to stimuli such as voluntary exercise with increased neurogenesis. Prominin1+/GFAP+ cells also exist in the adult human DG, the only region in the human brain for which adult neurogenesis has been consistently reported. Our data, together with previous evidence of such double-positive NSCs in the developing murine brain and in neurogenic regions of vertebrates with widespread neurogenesis, suggest that Prominin1- and GFAP-expressing cells are NSCs in a wide range of species in development and adulthood.
EVALuna2:22282